2013
DOI: 10.1007/s11274-013-1267-7
|View full text |Cite
|
Sign up to set email alerts
|

Management of soybean oil refinery wastes through recycling them for producing biosurfactant using Pseudomonas aeruginosa MR01

Abstract: Biosurfactant production through a fermentation process involving the biodegradation of soybean oil refining wastes was studied. Pseudomonas aeruginosa MR01 was able to produce extracellular biosurfactant when it was cultured in three soybean oil refinement wastes; acid oil, deodorizer distillate and soapstock, at different carbon to nitrogen ratios. Subsequent fermentation kinetics in the three types of waste culture were also investigated and compared with kinetic behavior in soybean oil medium. Biodegradati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…Moreover, the CSL alone did not support the bacterial growth and hence biosurfactant production. And a CSL concentration of more than 5mL/L suppressed biosurfactant secretion ( Table), likely originating from a relationship between biosurfactant production yield and C/N ratio [25,26]. The significant upper and lower limits of carbon and nitrogen sources construed from the one-factor-at-a-time step are summarized in Table . Data from the factorial design were subjected to multiple regression analysis using least squares regression methodology by Box-Behnken design.…”
Section: Optimization Design and Results By Rsm Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the CSL alone did not support the bacterial growth and hence biosurfactant production. And a CSL concentration of more than 5mL/L suppressed biosurfactant secretion ( Table), likely originating from a relationship between biosurfactant production yield and C/N ratio [25,26]. The significant upper and lower limits of carbon and nitrogen sources construed from the one-factor-at-a-time step are summarized in Table . Data from the factorial design were subjected to multiple regression analysis using least squares regression methodology by Box-Behnken design.…”
Section: Optimization Design and Results By Rsm Methodologymentioning
confidence: 99%
“…The total cost of raw materials and the productivity of biosurfactant produced by P. aeruginosa MR01 in different processes have been shown in table 7 [20,21,25,34].…”
Section: Coefficients a B And CD In Equation Ofmentioning
confidence: 99%
“…One economic survey indicated that the cost of the raw materials accounted for 50% of the total production costs of biosurfactant . One strategy to overcome the expense of raw materials would be to use water‐immiscible wastes such as the vegetable oil residues from refinery plants . These residues not only lead to economic losses for the industry, but constitute an environmental hazard.…”
Section: Introductionmentioning
confidence: 99%
“…Reuse and recycling activities of heavy metals can reduce the demand for raw materials and energy while minimizing the impact of waste disposal [11]. Although the method of incineration is rather progressive (most of the hazardous components are transformed into less dangerous substances, combined with volume reduction), but there are some harmful side effects such as sulphur and nitrogen oxides, hydrogen chloride, dioxins, heavy metals compounds, ash and other materials are generated which causes groundwater pollution and contamination [12].…”
Section: Introductionmentioning
confidence: 99%